Use of the National Museum as a Learning Resource for Social Science Subjects - Ahmad, Andy; Jubaedah, Siti; Fajarianto, Otto; Nurlia, Titim (Journal Socio Humanities Review, 2022)
Social studies subjects are one of the subjects that must be passed by students from elementary to high school levels. History subjects at the high school level are about building students' awareness of the importance of time and place which is a process from the past, present and future, training students' critical power to understand facts, concepts and generalizations correctly based on a scientific and methodological approach. science. However, what happens in the learning process in schools does not pay attention to these goals so that students do not understand social studies. This study aims to provide a theoretical basis that in the learning process can use various sources in social studies subjects, namely museums. Museums are places where valuable items from the past are exhibited that can support the learning process. The national museum is one of the museum facilities that can be used. From various learning theories and the cone of Dale's experience, it shows that there are good results if learning is based on learning by doing.